Tradição e modernismo em Prefácio Interessantíssimo de Mário de Andrade (Polifonia, 1997)
ABSTRACT: This paper examines the presence of tradition in Prefácio interessantíssimo of Mário de Andrade. Combing through the past, authors, literary works and ancient theories are revised at several moments in the preface of Paulicéia Desvairada, attesting to the impossibility of conceiving the absolute original and creating the new from nothing.